Representation of Liberation War in the Films of 90s - ShifatSumaiya; AhmedSalma (Communications. Media. Design, 2019)
In the history of Bangladesh, the liberation War of 1971 is an unforgettable period. Through the bloody struggle of nine months their independence is achieved, which simultaneously contains the spirit of Bengali spirit, love and patriotism towards the motherland. Bangladeshi people participated in the spirit of love and extreme sacrifice from every sphere of society for the motherland and Bengali language. In addition to other mass media, film is an equally important medium and in films there is a great deal of effort to uncover the vital role of creating ideas and consciousness among people about the liberation War. With this in mind, this study tried to find out, how the films conceptualise the spirit and history of the liberation War in the 90s after two decades of freedom. This study has been conducted taking three feature films of the 90s based on the liberation war. Adopting the content analysis method, the study aimed to answer two questions- ‘How do the films of the 90s represent the liberation War of Bangladesh?’; and, ‘To portray the history of the liberation war, what kind of content and contexts have been used in these films?’ The results showed that the films of the nineties signify the jana-itihas of Bangladesh by attaining the concept of the liberation War in a distinctive way. With symbolic representation of the war and cultural contexts, these films signify the jana-itihas of Bangladesh for passing information from generation to generation.